The Official Patient's Sourcebook on Locked-In Syndrome Elektronische Ressource - Parker, James N; Parker, Philip M (San Diego : ICON Group International Inc, 2004)
This book has been created for patients who have decided to make education and research an integral part of the treatment process. Although it also gives information useful to doctors, caregivers and other health professionals, it tells patients where and how to look for information covering virtually all topics related to locked-in syndrome (also Cerebromedullospinal Disconnection; De-Efferented State; Pseudocoma), from the essentials to the most advanced areas of research. The title of this book includes the word official. This reflects the fact that the sourcebook draws from public, academi